The graphic novel : an introduction - Baetens, Jan.; Frey, Hugo. (New York : Cambridge University Press, 2015)
"This book provides both students and scholars with a critical and historical introduction to the graphic novel. Jan Baetens and Hugo Frey explore this exciting form of visual and literary communication, showing readers how to situate and analyze graphic novels since their rise to prominence half a century ago. Several key questions are addressed: What is the graphic novel? How do we read graphic novels as narrative forms? Why is page design and publishing format so significant? What theories are developing to explain the genre? How is this form blurring the categories of high and popular literature? Why are graphic novelists nostalgic for the old comics? The authors address these and many other questions raised by the genre. Through their analysis of the works of many well-known graphic novelists - including Bechdel, Clowes, Spiegelman and Ware - Baetens and Frey offer significant insights for future teaching and research on the graphic novel"--
Machine generated contents note: 1. Introduction to the graphic novel: a special type of comic book; 2. Adult comics before the graphic novel: from moral panic to pop art sensationalism, 1945-67; 3. Underground comix and mainstream evolutions, 1968-80; 4. 'Not just for kids': clever comics and the new graphic novels; 5. Understanding panel and page layouts; 6. Drawing and style, word and image; 7. The graphic novel as a specific form of storytelling; 8. The graphic novel and literary fiction: exchanges, interplays and fusions; 9. Nostalgia and the return of history.
boek